Effect Of Aging Time, Calcination And Sintering Temperature To Β-Tricalcium Phosphate (Β-Tcp) - Redin, Hanna Bakar (2019)
β-TCP has a higher resorption rate and it is normally considered as a biodegradable materials that allows bone growth and replacement. In this study, β-TCP was synthesized through sol-gel method. Thus, the objectives of this study were to determine the effect of aging time and temperature towards the formation of β-TCP phase and effect of sintering temperature on the properties of β-TCP pallet. To synthesize β-TCP powder, 0.0926 mol of calcium nitrate tetrahydrate, Ca(NO3)2.4H2O, 0.0926 mol citric acid monohydrate C6H8O7.H2O and 0.0617 mol of di-ammonium hydrogen phosphate (NH4)2HPO4 were used. Parameter that were studied include two aging time, 24 hours and 48 hours and five calcination temperature; 500ºC, 600ºC, 700ºC, 800ºC and 900ºC. Powder were characterized via thermogravimetric-differential scanning calorimetry (TG-DSC), X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) and fourier transform infrared spectroscopy (FTIR). Powder with highest formation of β-TCP were pressed into pallet form and sintered at 1000ºC and 1100ºC. Final characterization and testing including bulk density and porosity test, shrinkage analysis, diametral tensile strength (DTS) test and simulated body fluid (SBF) test were performed on sintered pallet. From the analysis, powder calcined at 900ºC with 48 hour ageing time shows the highest formation of β-TCP (83.9 wt%) while 500ºC with 24 hours aging time shows the lowest β-TCP formation (41.2wt%). It shows that increasing trend of β-TCP phase with the increase of calcination temperature. Full surface area of apatite layer formed after 7th day immersion of sintered pallet at 1100 ºC in SBF solution. This prove that β-TCP is bioactive and biocompatible material.